An Aluminum Hydride That Functions like a Transition‐Metal Catalyst1. (18th June 2015) - Yang, Zhi; Zhong, Mingdong; Ma, Xiaoli; De, Susmita; Anusha, Chakkittakandiyil; Parameswaran, Pattiyil; Roesky, Herbert W.
Abstract The reaction of [LAlH2] (L=HC(CMeNAr)2, Ar=2, 6‐iPr2C6H3) with MeOTf (Tf=SO2CF3) resulted in the formation of [LAlH(OTf)] (1) in high yield. The triflate substituent in 1 increases the positive charge at the aluminum center, which implies that 1 has a strong Lewis acidic character. The excellent catalytic activity of 1 for the hydroboration of organic compounds with carbonyl groups was investigated. Furthermore, it was shown that 1 effectively initiates the addition reaction of trimethylsilyl cyanide (TMSCN) to both aldehydes and ketones. Quantum mechanical calculations were carried out to explore the reaction mechanism.